PENGEMBANGAN MEDIA PEMBELAJARAN PEMAHAMAN MEMBACA BAHASA PRANCIS SETARA A2 BERBASIS TECHNO PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) - Marice Marice; Isda Pramuniati; Jubliana Sitompul (MEDIA DIDAKTIKA, 2019)
The purpose of this study is to develop a reading media in French with A2 based on Pedagogical Technology and Content Knowledge (TPACK). Development of learning media needs to be done to improve technology development in the world of education launched by the millennial era of the Industrial Revolution 4.0. In addition, KKNI at Medan State University interviewed technology that was in accordance with the concepts and learning, the results of learning to read in French, students were still low, learning media had not used new technology. This research was conducted in the Unimed Faculty of Language and Arts French Education Program studio with the implementation of the Plomp model (1997: 6-15) through the empathy phase, namely (1) the investigation phase, (2) the design phase, (3) the implementation or construction phase, ( 4) test, evaluation and revision phases. The investigation phase related to the development of learning media in reading French, A2, is also done with learning material, besides that it is carried out in the form of data that discusses material that contains material or material sent into learning media developed using Windows Movie Maker, video applications pad, which is then uploaded to the FBS E-Learning network. Application that is used by instructors to construct content, organize quizzes, assignments, and manage communication with learners. The results obtained through this study are learning media developed with TPACK and online learning-based and face-to-face learning content in Reading Comprehension courses in French equivalent of A2 in the FBS Unimed French Language Study program.